MEMRISE APPLICATION AS DIGITAL MEDIA SKILLTO ENRICH STUDENTS’ ENGLISH VOCABULARYAT JUNIOR HIGHSCHOOL IN MEDAN - Bambang Nur Alamsyah Lubis; Azizah Husda; Putri Annisa Zulhantiar (Jurnal Education and Development, 2023)
This study deals with the use of the Memrise application in enrichment students’ English vocabulary. This study is conducted based on a preliminary study which showed that students had difficulty learning English due to their lack of vocabulary. The objective of the study is to find out the significant effect of Memrise application in enriching students’ English vocabulary. The method that is used to conduct the research is quantitative method. The sample of the research is eight grade students at SMP Dharma Pancasila Medan. The instruments to collect the data are pre-test and post-test. The data analysis techniques of this study were (1) normality test (2) homogeneity test (3) hypothesis testing in the form of t-test. Hypothesis testing uses the t-test formula which is preceded by a normality test and a homogeneity test. The results of the t-test shows that there is a significant effect to enrich student English vocabulary at SMP Dharma Pancasila Medan, the value sig (2-tailed) = 0.001 < 0, 05 then H0 is rejected and Ha is accepted